EFL Students’ Speaking Achievement And Its Relationship With Epistemic Beliefs - Emaliana, Ive; Rohmah, Kholifatur (IJET (Indonesian Journal of English Teaching), 2020)
The purpose of the present research is to uncover relationship between English as a Foreign Language (EFL) students' speaking score achievement and their epistemic beliefs. To this end, 63 Indonesian EFL students completed two different instruments, namely EFL epistemic beliefs questionnaire and final test of Intensive Speaking course. The results of Pearson Product Moment Correlation demonstrated that speaking achievement is significantly correlated with epistemic beliefs adapted from Emaliana (2017), consisting seven sub dimensions, namely, fix ability, certain knowledge, simple knowledge, omniscient authority, learning and communication strategies, foreign language aptitude, and motivation and expectation. Likewise, the findings manifested that sophisticated students who are indicated by high level of epistemic beliefs outperform simple students, who are otherwise having low level of epistemic beliefs. This research holds significant implications for curriculum, teaching and learning materials and instructional media developers, as well as teachers to afford students with personal beliefs about knowledge and knowing EFL to enhance the students' speaking skill.